2013
DOI: 10.1523/jneurosci.3169-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Essential Thalamic Contribution to Slow Waves of Natural Sleep

Abstract: Slow waves represent one of the prominent EEG signatures of non-rapid eye movement (non-REM) sleep and are thought to play an important role in the cellular and network plasticity that occurs during this behavioral state. These slow waves of natural sleep are currently considered to be exclusively generated by intrinsic and synaptic mechanisms within neocortical territories, although a role for the thalamus in this key physiological rhythm has been suggested but never demonstrated. Combining neuronal ensemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
171
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(193 citation statements)
references
References 62 publications
(4 reference statements)
14
171
0
Order By: Relevance
“…However, because ML218 effects were found, regardless of the distance of the microinjections to the reticular nucleus (see Fig. 4), we believe that most of the changes described in our study were due to local drug effects in the basal ganglia-receiving territory of the thalamus (David et al 2013;Li et al 2005).…”
Section: Potential Study Limitationsmentioning
confidence: 54%
See 1 more Smart Citation
“…However, because ML218 effects were found, regardless of the distance of the microinjections to the reticular nucleus (see Fig. 4), we believe that most of the changes described in our study were due to local drug effects in the basal ganglia-receiving territory of the thalamus (David et al 2013;Li et al 2005).…”
Section: Potential Study Limitationsmentioning
confidence: 54%
“…The identification of these was based on literature indicating that the mechanisms underlying the induction of LTS bursts lead to a progressive increment of the ISIs inside of the burst (see Fig. 5C3), referred to as the descelerando signature (David et al 2013). Bursts that failed to meet the criteria of rebound bursts were defined as non-rebound bursts.…”
Section: Electrophysiologymentioning
confidence: 99%
“…However, recent evidence suggests that thalamic bursting plays a fundamental role in sensory processing (53,54). Studies of visual (55) and somatosensory (30,53) pathways demonstrate the presence of thalamic bursting in awake and attentive states, implying that bursting activity modulates sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings in deafferented cortex show that slow oscillations can occur in the absence of thalamic connections (22). Yet basic functional anatomic and neurophysiological reasoning suggests that the thalamus is likely a significant participant in slow and δ oscillations (23,24). To address these questions in the context of induction and emergence from propofol anesthesia, we analyzed the coherence between the superficial layer (2/3, referred to as SL) and deep layers (5 and 6, referred to as DLs), layers of prelimbic cortex, and the different high-order thalamic nuclei (M, C, and S).…”
Section: Layers Of Prefrontal Cortex Are Differentially Affected By Pmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14).…”
mentioning
confidence: 99%